Once-monthly paliperidone injection for the treatment of schizophrenia - Delia Bishara (Dove Medical Press, 2010)
Delia BisharaPharmacy Department, South London and Maudsley NHS Foundation Trust, London, United KingdomAbstract: Paliperidone palmitate is a new long-acting antipsychotic injection for the treatment of acute and maintenance therapy in schizophrenia. Paliperidone (9-hydroxyrisperidone) is the major active metabolite of risperidone and acts at dopamine D2 and serotonin 5HT2A receptors. As with other atypical antipsychotics, it exhibits a high 5HT2A:D2 affinity ratio. It also has binding activity as an antagonist at α1- and α2 adrenergic receptors and H1 histaminergic receptors, but has virtually no affinity for cholinergic receptors. Paliperidone palmitate has been shown to be effective in reducing Positive and Negative Syndrome Scale total scores in four short-term trials in acute schizophrenia. It was also effective as maintenance therapy in a long-term trial in which time to recurrence of symptoms was significantly longer in paliperidone-treated patients compared with placebo. In addition, paliperidone was shown to be noninferior to risperidone long-acting injection in one study, but this noninferiority was not established in another longer study comparing the two drugs. Treatment should be initiated with 234 mg on day 1 and 156 mg on day 8, followed by a recommended monthly maintenance dose of 39–234 mg based on efficacy and tolerability. Paliperidone palmitate is generally well tolerated, although it can cause weight gain and a rise in prolactin levels, which is generally greater in women than in men. Overall, paliperidone palmitate may have advantages over other currently available long-acting injections, and therefore may be a useful alternative for the treatment of schizophrenia, although further long-term trials comparing it with active treatments are warranted.Keywords: paliperidone palmitate, injection, schizophrenia, long-acting